Challenges in the development of future treatments for breast cancer stem cells - Shyam A Patel (Dove Medical Press, 2010)
Shyam A Patel1,2, Anicia Ndabahaliye2, Philip K Lim2, Russell Milton2, Pranela Rameshwar21Graduate School of Biomedical Sciences, 2Department of Medicine – Division of Hematology/Oncology, New Jersey Medical School, University of Medicine and Dentistry of New Jersey, Newark, NJ, USAAbstract: The recurrence of tumors after years of disease-free survival has spurred interest in the concept that cancers may have a stem cell basis. Current speculation holds that as few as 0.1% of the tumor mass may be chemoresistant and radioresistant, harboring stem-like properties that drive tumor survival, development, and metastasis. There are intense investigations to characterize cancer stem cells on the basis of self-renewal and multi-lineage differentiation. Thus far, no successful targeted therapies have been developed and reached the clinic, but as these cells are isolated and characterized, insights may be unraveled. In this review, we discuss the controversy over the origins of the cancer stem cell hypothesis and the unforeseen factors that may facilitate breast cancer stem cell survival and metastasis. We discuss the role of tumor microenvironment, including carcinoma-associated fibroblasts, epigenetic factors, and the Th1/Th2 balance, in supporting breast cancer stem cells. In addition, we have incorporated ideas on the epithelial-to-mesenchymal transition in metastatic dissemination of epithelial malignancies. This area is relevant since breast cancer stem cells have been suggested to revert to a mesenchymal phenotype during the progression of cancer. Finally we discuss prospects of developing targeted therapy including novel treatment modalities such as oncolytic viral therapy, differentiation therapy, and nanotechnology.Keywords: cancer stem cells, EMT, oncolytic viral therapy, microenvironment, side population, crosstalk